Perceptions of university teachers on the difficulties associated with the use of masks. Towards a more pragmatic approach to the prevention of dysphonia in teachers - Castejón , Luis; Morales-Sánchez, Celia; Díaz-Fresno, Estefanía; Martínez-López, Verónica (Revista de Investigación en Logopedia, 2024)
Voice difficulties associated with the abuse and misuse of the voice during class are experienced at the onset of the vocal disorder. Knowledge of the perceptions of these difficulties by voice professionals is relevant for designing proposals for the prevention of occupational dysphonia. The mandatory use of the orofacial mask in the health crisis caused by COVID-19 generated an ideal situation to study the perceptions and reactions of university professors to voice difficulties. A convenience sample of 168 university professors responded to a questionnaire that collected information on the effect of mask use on teaching, communication, and voice. The results indicate that the use and care of the voice are subject to communicative effectiveness, which is the main purpose of university teaching. In addition, in the face of perceived vocal difficulties, the compensation strategies that teachers activate are scarce. The perceptions identified in this research, as in other previous studies, are more influenced by biological (sex) and psychological (perceived anxiety) variables than by factors directly associated with the use of the voice during class (noise, number of students, class duration). The implications of the results for the design of dysphonia prevention are discussed, suggesting a pragmatic shift in the prevention. This shift proposes to subordinate instruction on hygiene and vocal technique to the practice of the communicative use of the voice during the class.
Keywords: Professional dysphonia; university teachers; voice difficulties; orofacial mask; prevention of dysphonia